1999
DOI: 10.1046/j.1469-8137.1999.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increased deposition of atmospheric nitrogen on Calluna vulgaris in upland Britain

Abstract:  Regular (monthly) additions of NH% NO $ (4-12 g N m −# yr −" ) were made over a period of 8 yr to areas of moorland in North Wales dominated by the ericaceous shrub Calluna vulgaris. Results from the early stages of the experiment have shown marked and dose-related increases in shoot extension and canopy height in response to the nitrogen treatments, with significantly higher shoot nitrogen contents. The nitrogen-related stimulation in the growth of the C. vulgaris canopy over this period has resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
5

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 29 publications
6
91
5
Order By: Relevance
“…In this case, the available carbon is invested in growth rather than in defence. It is well established that nitrogen addition increases nitrogen concentrations in heather, C. vulgaris (Berdowski and Siepel 1988;Duncan et al 1994;Hartley et al 1995;Carrol et al 1999;Gordon et al 1999) and other ericaceous plants (Mallik 1996;Prescott et al 1993;Nordin et al 1998). However, the expected decrease in total phenolics or condensed tannin levels due to solely nitrogen additions has not yet been empirically shown either in the greenhouse or in the field (Iason and Hester 1993;Hartley et al 1995;Kerslake et al 1998;Bradley et al 2000;Alonso et al 2001;Hansen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the available carbon is invested in growth rather than in defence. It is well established that nitrogen addition increases nitrogen concentrations in heather, C. vulgaris (Berdowski and Siepel 1988;Duncan et al 1994;Hartley et al 1995;Carrol et al 1999;Gordon et al 1999) and other ericaceous plants (Mallik 1996;Prescott et al 1993;Nordin et al 1998). However, the expected decrease in total phenolics or condensed tannin levels due to solely nitrogen additions has not yet been empirically shown either in the greenhouse or in the field (Iason and Hester 1993;Hartley et al 1995;Kerslake et al 1998;Bradley et al 2000;Alonso et al 2001;Hansen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the earlier years, both bryophytes and lichens had disappeared from below the C. vulgaris canopy in all nitrogen addition treatments, although Vaccinium myrtillus maintained its cover (Carroll et al, 1999). It is not certain, however, whether this was a response to direct effects of nitrogen addition or through changes in C. vulgaris canopy architecture and increased litter production resulting in reduced light penetration.…”
Section: (A) Effects On Growth and Species Compositionmentioning
confidence: 78%
“…The following three years of the study, however, showed a much reduced effect of the treatment on shoot extension, and no clear dose response to increasing nitrogen inputs. The 1996 data in particular showed no effect of nitrogen on shoot extension at all (Carroll et al, 1999). One interpretation of the C. vulgaris growth responses in this experiment is that addition of N has accelerated the natural C. vulgaris cycle, with earlier ageing and opening of the canopy in the highest treatment plots.…”
Section: (A) Effects On Growth and Species Compositionmentioning
confidence: 84%
See 2 more Smart Citations